PERBEDAAN PENGARUH LATIHAN SKIPING DAN INTERVAL TRAINING TERHADAP PENINGKATAN VO2 MAX PADA PEMAIN SEPAKBOLA - Ahmad Fakih Prasetyo; Tyas Sari Ratna Ningrum; Lailatuz Zaidah (Bajang Institute, 2025)
Background: Background: VO2 max or maximal oxygen volume is the main indicator of a person's aerobic capacity and has a vital role in athlete performance, especially in soccer. Therefore, developing VO2 max is a key component in modern soccer training programs. Physiotherapy interventions through skipping exercises and interval training are non-pharmacological approaches that can be used to increase VO2 max effectively. Research Objective: To determine the differences in the effects of skipping exercises and interval training on increasing VO2 max in soccer players. Method: This study is an experimental quantitative study with a pre-test and post-test control group design. The sample consisted of 22 male respondents from Baturetno Football School students who were divided into two groups (11 respondents each). The intervention was carried out 3x a week for 4 weeks. VO2 max data were collected using the Multi Stage fitness test (MFT). Statistical tests using Paired Sample T-Test and Independent Sample T-Test. Results: Hypothesis I and II tests using paired sample t-test showed that there was an effect of skipping and interval training on increasing VO2 max in soccer players (P = 0.00 P <0.05). Hypothesis III tests using independent sample t-test showed that interval training had a greater effect than skipping training on increasing VO2 max in soccer players. (P = 0.008 P <0.05). Conclusion: interval training had a greater effect than skipping training on increasing VO2 max in soccer players. Suggestion: Further research is expected to conduct further analysis on other, more varied exercises to increase VO2 max in soccer players